INSECTICIDAL AND OXIDATIVE EFFECTS OF AZADIRACHTIN ON THE MODEL ORGANISM Galleria mellonella L. (LEPIDOPTERA: PYRALIDAE) - NURULLAHOĞLU, ZAHİDE ULYA (WILEY, 2015)
The insecticidal effects, specifically, changes in hemolymph total protein and malondialdehyde (MDA) levels, and antioxidant enzyme activities of azadirachtin (AZA) given to the wax moth, Galleria mellonella L. (Lepidoptera: Pyralidae) larvae via force feeding were investigated. Bioassays showed that the LD50 and LD99 (lethal dose) values of AZA were 2.1 and 4.6 mu g/larva, respectively. Experimental analyses were performed with five doses of AZA (0.5, 1, 1.5, 2, and 3 mu g/larva). Total protein level in larval hemolymph increased at all AZA doses at 24 h whereas a considerable decrease was observed at 2 and 3 mu g/larva doses, and only an increase displayed at 1.5 mu g/larva at 72 h. The level of MDA increased at 2 and 3 mu g/larva doses at 24 h compared with controls. This trend was also observed at 1.5, 2, and 3 mu g/larva doses at 72 h and MDA levels were lower when compared with those of 24 h at all doses except for 1.5 mu g/larva dose. Catalase activity decreased at 1, 1.5, and 2 mu g/larva doses at 24 h whereas increased at all doses except for 0.5 mu g/larva at 72 h compared with controls. AZA led to a decline in superoxide dismutase activity at all experimental doses at 24 and 72 h except for 3 mu g/larva doses at 72 h. An increase in glutathione-S-transferase (GST) activity was evident at all AZA doses at 24 h. AZA displayed 68% decline in GST activity at 72 h post treatments when compared to 24 h. Consequently, We infer that the toxicity of AZA extends beyond its known actions in molting processes to redox homeostasis. (C) 2015 Wiley Periodicals, Inc.
Keywords: azadirachtin; allelochemical; Galleria mellonella; force feeding; antioxidative enzyme; POSTEMBRYONIC DEVELOPMENT; AQUEOUS EXTRACT; STRESS; CYPERMETHRIN; HYMENOPTERA; MECHANISMS; ENDOSULFAN; RESPONSES; TISSUES; SYSTEMS